Floristic composition in headwaters areas of the Piauitinga river Sub-Basin in Sergipe, Brazil (Research, Society and Development, 2022)
Despite the riparian forest importance, it is evident that areas compose sub-basins undergo constant changes, culminating in these ecosystems’ degradation. Thus, the floristic composition of nine headwaters of the Piauitinga River Sub-Basin, located in Sergipe, Brazil, will be presented. A collection of botanical material was taken within a radius of 50 m from the water edge of each source. The taxonomic identification of the specimens was developed considering specialized literature, taxonomic keys, expert consultation, comparison with dissected perianth and queries to the Virtual Herbarium. There were 190 species of vascular plants distributed in 146 genera and 55 families. 188 species of the Angiosperms group with 144 genera and 51 botanical families and the pteridophytes are represented by two species, belonging to two genera and two families. It is recommended the use of ecological restoration models that contemplate such species in future projects to be relayed in this planning unit.